Romanian Banks – Romanian SMEs: A Mutual Business Relationship - Ion POPA; Camelia Elena CIOLAC; Sebastian CEPTUREANU; Eduard CEPTUREANU (Revista de Management Comparat International)
This paper analyzes the bank-SMEs partnership in terms of ICT collaboration. The data about ICT projects developed in the Romanian banks having SMEs as a technology provider is collected by web content mining. Then, the paper addresses two main perspectives. At first, we identify the features that characterize the successful SMEs that managed to develop business relationships with the Romanian Banks and we build an econometric model to express this dependency. On the other hand, the paper analyzes the problem from the Romanian banks’ perspective, identifying patterns in their IT investment decisions.